2002
DOI: 10.1046/j.1365-2591.2002.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscopic study of dentinal erosion by final irrigation with EDTA and NaOCl solutions

Abstract: Final irrigation with 6% NaOCl accelerates dentinal erosion following treatment with 15% EDTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
149
1
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 17 publications
9
149
1
18
Order By: Relevance
“…42 This information has to be interpreted with care, as the removal of smear layer in the apical region remains unpredictable. 20,43 The latter was also the case in the present study ( Fig. 1c and d).…”
Section: S-46supporting
confidence: 89%
See 1 more Smart Citation
“…42 This information has to be interpreted with care, as the removal of smear layer in the apical region remains unpredictable. 20,43 The latter was also the case in the present study ( Fig. 1c and d).…”
Section: S-46supporting
confidence: 89%
“…EDTA rinsing solution used as a final rinse provides effective smear-layer removal. 19,20 Irrigants that can remove the smear layer allow penetration of sealers into dentinal tubules.…”
mentioning
confidence: 99%
“…On the other hand, erosion can also help optimize the cleaning of the canal wall, eliminating debris and bacteria from the endodontic space. 16,34 Although the CA and PA groups caused greater erosion in dentinal tubules when compared to the EDTA and QMiX groups, these solutions did not significantly change microhardness at 500 µm. According to Saghiri et al, 12 erosion is not the main cause of reduction in dentin hardness, as the depth of irrigant penetration might be the key factor.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, this association leads to dentinal tubule orifice opening, intertubular dentinal erosion (12,20) and dentin microhardness reduction (21). When NaOCl was used alone as an irrigating agent, the exposed inorganic material prevented further dissolution of dentine.…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al (20) demonstrated that final irrigation with 6% NaOCl after treatment with 15% EDTA causes erosion of peritubular and intertubular dentin. Surface dentin was neither smooth nor flat and dentinal tubule orifices were irregularly enlarged (20).…”
Section: Discussionmentioning
confidence: 99%